Penerapan Program Menghafal Juz 'Amma Sebagai Syarat Ujian Skripsi Pada Program Studi Pendidikan Guru Sekolah Dasar Di Universitas Muhammadiyah Surakarta - Latifah, Nuri; , Minsih, S.Ag., M.Pd (2017)
This study aims to describe the implementation of the memorizing program of juz amma by the students of the Elementary School Teacher Education Studies Program at the Muhammadiyah University of Surakarta, and identifies the constraints and solutions. The type of this research is qualitative research. Data collection techniques used are structured interviews, observation and documentation. This research uses data validity test with triangulation. Data analysis techniques with reduction, display data and conclusions / verification. The results of this study indicate that: 1) the memorization of juz 'amma program in Primary School Teacher Education at Muhammadiyah University of Surakarta begins in 2015 based on the joint decision of the lecturers during the work meeting. This program is used as a thesis examination requirement because it is to encourage students to memorize it, aiming to improve reading, reproduce and improve students' faith. Memorization juz 'amma will be tested memorized when going to carry out thesis exams as the accountability of students in implementing the program memorize juz' amma. 2) the obstacles that arise is still a lot of students who are indifferent to this program so many students who have not memorized until the exam is a thesis, the solution used using the programs that have been used by students of Primary School Teacher Education Studies program such as regular reading of the letter -surat in juz 'amma that has been scheduled every will start daily lectures, and use other methods of lecturers who apply other methods and HMP create programs related to how to memorize juz' amma easily and quickly. For students who have thesis exams but belom can memorize the letter requested by the lecturer testers eat must deposit at the time will ask for the signature of revision after thesis examination.